ANALISIS BENTUK DUKUNGAN KELUARGA TERHADAP KONSEP DIRI ORANG DENGAN HIV DI VCT RUMAH SAKIT DEMANG SEPULAU RAYA KABUPATEN LAMPUNG TENGAH (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2023)
Someone who has Human Immunodeficiency Virus (HIV) has psychological problems that will affect their self-concept; in one study, it was found that 70% of HIV patients experienced a negative self-concept. The impact of a negative self-concept can lead to low levels of compliance with PLWHA doing ARV treatment. Family support is one factor that supports the dimensions of a person's self-concept. This study aims to identify forms of family support for the self-concept of people living with HIV. This type of research is quantitative with a cross-sectional approach. The population of all people with HIV, with a sample of 75 people, was taken by total sampling. The study was conducted at the VCT of Demang Se Island Raya Hospital, Central Lampung Regency, in May-June 2022. Data collection used a questionnaire. Data analysis was univariate, bivariate (chi-square test), and multivariate (logistic regression). The results obtained negative self-concept at as much as 60%, negative emotional support at 76%, negative rewards at 69.3%, positive material at 53.3%, and negative information at 70.7%. There is a relationship between emotional support (p-value = 0.002), esteem support (p-value = 0.005), and material support (p-value = 0.021) in the self-concept of people with HIV, and there is no relationship between informational support and the self-concept of people living with HIV. Value (p-value = 0.123) and the dominant factor in the research in this study is emotional support, which has the highest OR value of 7.252. It is recommended that families provide emotional support for people living with HIV by participating in activities organized by the community of people living with HIV.